Impact of prophylactic cranial irradiation on pattern of brain metastases as a first recurrence site for limited-disease small-cell lung cancer. (9th August 2018) - Nakamura, Masaki; Onozawa, Masakatsu; Motegi, Atsushi; Hojo, Hidehiro; Zenda, Sadamoto; Nakamura, Naoki; Udagawa, Hibiki; Kirita, Keisuke; Matsumoto, Shingo; Umemura, Shigeki; Yoh, Kiyotaka; Niho, Seiji; et al.
Abstract: This study sought to evaluate the impact of prophylactic cranial irradiation (PCI) on the pattern of brain recurrence after radical treatment in patients with limited-disease small-cell lung cancer (LD-SCLC). Patients treated with radiotherapy and chemotherapy between January 2006 and December 2014 at a single institution were retrospectively examined. Radiotherapy was performed using accelerated hyperfractionated radiotherapy (twice daily, 45 Gy in 30 fractions) or conventional fractionated radiotherapy (once daily, 50 Gy in 25 fractions). The chemotherapy regimen consisted of intravenous platinum–etoposide. A total of 162 patients were included and the median follow-up duration was 38 months. Ninety-three patients underwent PCI, and the 3-year overall survival (OS) rates were 14% among patients without PCI and 41% among those with PCI ( P < 0.001). The frequency of brain metastases as a first recurrence site (BMFR) was significantly lower among patients who underwent PCI, compared with those who did not ( P = 0.002). The median time to the l of BMFR was significantly shorter among patients without PCI than among those with PCI ( P = 0.012). In addition, 68% of the BMFR patients who did not undergo PCI exhibited five or more lesions, while only 12% of BMFR patients who did undergo PCI exhibited five or more lesions ( P < 0.001). PCI had a significant positive impact on patient prognosis after radical treatment for LD-SCLC, and the difference in the number of, and time to the appearance of, BMFR between patients treated with PCI and those treated without PCI might affect the clinical outcomes.